2011
DOI: 10.1002/pip.1102
|View full text |Cite
|
Sign up to set email alerts
|

On the testing of large PV arrays

Abstract: This paper reports on the IES‐UPM experience from 2006 to 2010 in the field of the characterization of PV arrays of commercial large PV plants installed in Spain within the framework of the profitable economic scenarios associated to feed‐in tariff laws. This experience has extended to 200 MW and has provided valuable lessons to minimize uncertainty, which plays a key role in quality assurance procedures. The paper deals not only with classic I–V measurements but also with watt‐metering‐based procedures. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 9 publications
3
49
0
5
Order By: Relevance
“…The results ofthe present work have been compared to on-site measurements realized by the IES-UPM during the last years on more than 200 MW of PV modules equipping solar plants in Spain, Italy and France [28]. Among the modules manufacturers present on more than 25 installations ofthe datábase of BDPV, it was possible to identify 9 that were also measured by the IES-UPM.…”
Section: Validation Ofthe Results Against On-site Measurementsmentioning
confidence: 95%
See 2 more Smart Citations
“…The results ofthe present work have been compared to on-site measurements realized by the IES-UPM during the last years on more than 200 MW of PV modules equipping solar plants in Spain, Italy and France [28]. Among the modules manufacturers present on more than 25 installations ofthe datábase of BDPV, it was possible to identify 9 that were also measured by the IES-UPM.…”
Section: Validation Ofthe Results Against On-site Measurementsmentioning
confidence: 95%
“…Other authors have reported the real nominal power of PV modules to be on average 5% inferior to the nominal power stated by their manufacturer [28,31]. Globally, those differences between real power and nominal power suggest that it is profitable to implement quality control procedures to verify and improve the quality ofPV systems [32,33].…”
Section: Taue3mentioning
confidence: 99%
See 1 more Smart Citation
“…Voltage across the switch during the OFF state can be presented by Equation (23), which is depicted in Figure 7a. Current through the switch during the ON state can be expressed by Equation (24) which is shown in Figure 7b.…”
Section: Semi-z-source Inverter Working Principlementioning
confidence: 99%
“…On the other hand, the use of transformer-less inverters reduces both the cost and size along with improved system efficiency. Some studies in particular [22,23] show that the transformer-less inverter increases the overall system efficiency by 2%. Besides, the requirement of galvanic isolation from low voltage utility grid becomes almost obsolete.…”
Section: Introductionmentioning
confidence: 99%